1999
DOI: 10.1038/sj.ejhg.5200312
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic aspects of phenylalanine hydroxylase deficiency in Spain: molecular survey by regions

Abstract: We present an extensive study of the genetic diversity of phenylalanine hydroxylase deficiency in the Spanish phenylketonuria population. We have analysed 195 PKU patients by DGGE analysis identifying 67 different mutations which represent 89% of the total mutant chromosomes. Seventeen mutations first described in Spain have not yet been detected elsewhere; ten of these are reported here for the first time. The clinical significance of this high genetic heterogeneity was examined by analysing the genotype-phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 21 publications
(24 reference statements)
4
40
1
Order By: Relevance
“…This loss of enzymatic function is most likely caused by conformational changes due to the presence of three additional amino acids (Gly-Leu-Gln) between the normal sequences encoded by exon 10 and exon 11 (Dworniczak et al, 1991). This mutation has been identified as the most common mutation in Mediterranean populations such as Turkey (Dobrowolski et al, 2011), Italy (Daniele et al, N. Ajami et al 2007), Spain (Desviat et al, 1999), Egypt (Effat et al, 1999), and Israel (Bercovich et al, 2008). In previous studies that have been performed in Iran, IVS10-11G>A was also identified with the highest frequency (Bonyadi et al, 2010;Zare-Karizi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This loss of enzymatic function is most likely caused by conformational changes due to the presence of three additional amino acids (Gly-Leu-Gln) between the normal sequences encoded by exon 10 and exon 11 (Dworniczak et al, 1991). This mutation has been identified as the most common mutation in Mediterranean populations such as Turkey (Dobrowolski et al, 2011), Italy (Daniele et al, N. Ajami et al 2007), Spain (Desviat et al, 1999), Egypt (Effat et al, 1999), and Israel (Bercovich et al, 2008). In previous studies that have been performed in Iran, IVS10-11G>A was also identified with the highest frequency (Bonyadi et al, 2010;Zare-Karizi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Expression analysis of PAH mutations also has the potential to shed light on genotype/phenotype relationships [Okano et al, 1991] and, in broad terms, such correlations exist [Kayaalp et al, 1997;Guldberg et al, 1998;Desviat et al, 1999]. There are, however, significant exceptions.…”
Section: In Vitro Expression Analysismentioning
confidence: 99%
“…Not included in Table 1 is mutation c.165delT, which has a relative allele frequency of 4% in Sicily. There are data for various regions of Spain, but the latest publication does not provide regional allele frequencies for the less common mutations [Desviat et al, 1999], and the national data for these mutations were taken from a previous publication . A separate study examined the PKU mutation frequencies in the eastern region of Catalonia; data from this study were corrected by a factor of 0.9 as apparently the total number of characterized (and not independent) chromosomes was taken as 100% [Mallolas et al, 1999].…”
Section: Italy Spain and Portugalmentioning
confidence: 99%